2017
DOI: 10.1186/s11671-017-2258-7
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Yolk-Shell Cu@C Nanocomposites as High-Performance Catalysts in Oxidative Carbonylation of Methanol to Dimethyl Carbonate

Abstract: A facile way was developed to fabricate yolk-shell composites with tunable Cu cores encapsulated within hollow carbon spheres (Cu@C) with an average diameter about 210 nm and cavity size about 80 nm. During pyrolysis, the confined nanospace of hollow cavity ensures that the nucleation-and-growth process of Cu nanocrystals take place exclusively inside the cavities. The size of Cu cores can be easily tuned from 30 to 55 nm by varying the copper salt concentration. By deliberately creating shell porosity through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…The Ren group reported a similar observation for the oxidative carbonylation of methanol to dimethyl carbonate. 103 It was found that larger void space in rattle-type Cu NPs on porous hollow carbon spheres structures led to higher activities compared to yolk–shell copper in hollow carbon spheres.…”
Section: Confinement By Encapsulationmentioning
confidence: 99%
“…The Ren group reported a similar observation for the oxidative carbonylation of methanol to dimethyl carbonate. 103 It was found that larger void space in rattle-type Cu NPs on porous hollow carbon spheres structures led to higher activities compared to yolk–shell copper in hollow carbon spheres.…”
Section: Confinement By Encapsulationmentioning
confidence: 99%
“…Several different types of LFYSNs were fabricated and used as model systems to determine their catalytic activity for several heterogeneous catalysis mainly for reduction and oxidation of nitro compounds, oxidation of alcohols and CO …”
Section: Applicationsmentioning
confidence: 99%
“…Carbon-supported copper is an effective catalyst in the oxidative carbonylation of methanol to dimethyl carbonate (DMC); however, in a slurry reaction system, the harsh reaction conditions often lead to agglomeration, loss, and oxidation of active copper species, which have a great influence on the catalytic activity and stability. In our previous studies, Cu@Carbon catalysts with controlled carbon shell thickness and Cu grain size have been prepared via one-step co-pyrolysis, ship-in-bottle, as well as hard template methods, , which displayed improved stability in the oxidative carbonylation of methanol. However, in a separated hollow carbon sphere, the problems of leaching and agglomeration of copper NPs still exist .…”
Section: Introductionmentioning
confidence: 99%